Analisis Optimasi Portofolio Saham Pada Index InfoBank15 di Era Pandemi Covid-19 - Aditya Rian Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to find out and analyze how many InfoBank15 index stocks are included in the optimal portfolio during the COVID-19 pandemic, and what is the optimal percentage of funds. The data processing method in this study uses the Markowitz model to determine InfoBank15 index stocks that are included as candidates for the optimal stock portfolio during the COVID-19 pandemic. The calculation results show that from 15 samples, there are only 5 (five) banking stocks that are members of the optimal portfolio, namely BBCA (Bank Central Asia Tbk), BBRI (Bank Rakyat Indonesia Tbk), BMRI (Bank Mandiri Tbk), BBNI (Bank Mandiri Tbk). Negara Indonesia Tbk), BBNI (Bank Negara Indonesia (Persero) Tbk) and BBTN (State Savings Bank). Investments in the optimal portfolio provide a total portfolio expected return of 4.877 percent with a portfolio risk/variance deviation rate of 0.255 percent